Unstable behaviour of pump-turbines and its effects on power regulation capacity of pumped-hydro energy storage plants. (October 2018) - Cavazzini, Giovanna; Houdeline, Jean-Bernard; Pavesi, Giorgio; Teller, Olivier; Ardizzon, Guido
Abstract: Intermittent renewable energy sources are characterized by a highly fluctuating, unpredictable and delocalized energy production, which significantly limits their penetration in the grid due to the great problems caused in the balance between demand and supply. Pumped Hydro Energy Storage plants represent an ideal solution because of their ability to provide large storage capacity with excellent grid connection properties, high cycle efficiency range and competitive costs. However, to provide primary and secondary regulation services, PHES have to increase their operation at part loads and to be able to switch fast and frequently between pump and turbine modes. At these operating conditions, pump-turbines suffer from behaviour instabilities, thereby constituting a limit when considering their exploitation in a wider continuous working range. So, the definition of a new concept of pump-turbines able to provide the full benefit of regulation in pumping mode and a wide range of power in generation mode is an urgent need to increase the exploitation of renewable energy sources. This paper clarifies the effects of the stable and unstable behaviour of pump-turbines on the power regulation capacity of pumped hydro energy storage plants, by presenting a description of the possible operating modes of PHES and by focusing on the impact of the hydraulic characteristics of pump-turbines on the capability of plant to start-up, shut-down or change its operating modes. A detailed review of the studies published in literature on the topic revealed the main characteristics of the hydraulic instabilities and the influence of one or more geometrical parameters on their onset. Even though some geometry modifications aimed at improving the RPT's stability in one operating mode were proposed in literature, the definition of a comprehensive design strategy, globally optimizing the pump-turbine design by considering simultaneously the complexity of the phenomena in both the operating modes, still represents a challenge. Highlights: clarifies the effects of the unstable behaviour of pump-turbines. presents a description of the operating modes encountered by a pump-turbine. highlights results, approaches and challenges in designing future pump-turbine.